Mirror activation pattern selection for energy efficient hexagonal QAM aided media-based modulation - Ozden, Burak Ahmet; Cogen, Fatih; Aydin, Erdogan (WILEY, 2023)
In this article, three mirror activation pattern (MAP) selection techniques are used to improve the performance of energy-efficient hexagonal quadrature amplitude modulation (HQAM) aided media-based modulation (MBM) system called HMBM. These three MAP selection (MS) aided HQAM techniques: (i) capacity-optimized MS-based HMBM (CMS-HMBM) scheme, (ii) MAP correlation (MC) aided MS-based HMBM (MMS-HMBM) scheme, (iii) Euclidean distance (ED) based MS aided HMBM (EMS-HMBM) scheme. MBM technique, one of the newest and most competitive candidates of the index modulation family, increases spectral efficiency linearly and significantly improves error performance. When MS techniques are integrated into telecommunication techniques, they significantly increase the performance of the system. Extensive computer simulations with Monte Carlo for the considered systems are performed on Rayleigh fading channels. The suggested system offers superior error performance than the conventional MBM scheme since it incorporates CMS, MMS, and EMS techniques. Additionally, the suggested new method offers greater energy efficiency than M$$ M $$-QAM constellation schemes since HQAM constellation schemes are by their very nature high energy efficiency. It is shown that the proposed CMS-HMBM, MMS-HMBM, and EMS-HMBM systems provide better error performance than capacity-optimized antenna selection (COAS) aided hexagonal spatial modulation (COAS-HSM), antenna correlation-based AS aided HSM (ACAS-HSM), Euclidean distance optimized AS aided HSM (EDAS-HSM), SM, and MBM systems for the same spectral efficiency. The suggested systems are envisaged for usage in sixth-generation and later wireless networks because of their high performance provided by the CMS, MMS, and EMS methods in the proposed system and the high spectral efficiency provided by the HMBM approach.
Keywords: ANTENNA SELECTION; INDEX MODULATION; SPATIAL MODULATION; SCHEMES; SPACE; TIME; Telecommunications